Pengaruh Meditasi Terhadap Hipertensi Pada Lansia di Banjar Angkling Desa Bakbakan Wilayah Kerja Puskesmas Gianyar II: The Effect of Meditation on Hypertension in The Elderly in Banjar Angkling Bakbakan Village, Gianyar II Public Health Center - Oktaviani, Ni Putu Wiwik; Urmilasari, Ni Putu Yessi; Trisnadewi, Ni Wayan; Adiputra, I Made Sudarma (Bali Medika Jurnal, 2021)
Introduction: Hypertension is the most common problem in elderly health and is a major cause of cardiovascular disease in the elderly. Meditation is used as an effort to treat hypertension by controlling the relationship and relaxing the blood vessels located in the vasomotor center in the spinal cord and as a relaxation meditation exercise that can reduce hypertension. The purpose of this study was to determine the effect of giving meditation on hypertension in the elderly. Method: This type of pre-experimental research with the design of One group Pre test-posttest Design. The total sample of 20 people was selected by purposive sampling technique. The tools used to collect data are a sphygmomanometer and a stethoscope. Result: The mean systolic blood pressure was 169.25 mmHg and diastole was 101.75 mmHg. The result shows the effect of giving meditation on hypertension in the elderly. Discussion: relaxation meditation which is centered on breathing will increase the circulation of oxygen to the muscles, so the muscles will relax, blood pressure will decrease.